Development and implementation of an on-demand competency-based onboarding program for clinical research professionals in academic medicine - Cranfill, Jessica R.; Deeter, Christine E.; Hannah, Deborah; Snyder, Denise C.; Freel, Stephanie A. (Frontiers in Medicine, 2023)
Over the past 7 years, Duke has implemented competency-based job classifications for clinical research professionals (CRPs) with a defined pathway for career advancement. The workforce is defined specifically as the collection of staff employed across the clinical research enterprise to operationalize clinical research and human participatory protocols through the hands-on conduct of protocol activities including participant enrollment, regulatory coordination, study documentation, data collection and management, and sponsor engagement. The competency framework for this critical workforce laid the foundation for a centrally developed on-demand onboarding program at Duke. The self-paced program is designed to engage learners through competency-based learning modules, guided mentor/manager discussions, and applied learning activities. Consisting of an initial E-Learning orientation to clinical research at Duke, called Express Start, followed by a 90-day role-based Onboarding Learning Plan, our onboarding program includes training in foundational pre-defined core competency areas and customizable learning paths. Associated Engagement Activity Packets for many clinical research competencies encourage mentor and/or manager involvement and hands-on learning for the employee through suggested enrichment activities. The program has been widely adopted for CRPs within the Duke University Schools of Medicine and Nursing, and newly hired CRPs and their managers have expressed satisfaction with these centrally offered tools. In this paper, we describe the methods used to develop and implement our competency-based onboarding program. We will share an evaluation of the program and planned next steps for expanding the suite of onboarding resources.